Comment on "An Active Plume Eruption on Europa During Galileo Flyby E26 as Indicated by Energetic Proton Depletions" by Huybrighs et al. Issue 6 (24th March 2021) - Jia, Xianzhe; Kivelson, Margaret G.; Paranicas, Christopher
Abstract: The Galileo spacecraft passed close to Europa on 11 encounters, two of which (E12 and E26) came within 400 km of the surface. In E12 data, there are perturbations in field and plasma data consistent with effects of a nearby plume (Jia et al., 2018). Huybrighs et al. (2020, https://doi.org/10.1029/2020GL087806 ) report depletions of proton flux in one channel of the Galileo Energetic Particle Detector (EPD) as Galileo passed close to Europa on E26. They trace particle trajectories in the magnetic field provided by a magnetohydrodynamic simulation and conclude that the spacecraft probably also passed through or close to a vapor plume on E26. However, the absence of a related signature in the measured magnetic field led us to question this conclusion. Examination of the EPD data remote from Europa on the E26 flyby reveals that the putative plume signature in the EPD data is an artifact. Plain Language Summary: In recent years, there have been reports that plumes, or extraterrestrial geysers, rise hundreds of kilometers above the surfaces of Saturn's moon, Enceladus, and Jupiter's moon, Europa. A very recent paper examines data from a close pass by Europa (E26 flyby) made by the Galileo spacecraft on January 3, 2000. The paper identifies a localized decrease in the count rate of energetic protons lasting about 20 s very near closest approach to Europa's surface and attributes the decrease to an interaction with a plume rising above Europa's surface. In this "comment" we demonstrate that a localized decrease of proton count rates is recorded at the same point in almost each measurement cycle (every 280 s) even very far from Europa on this pass due to an anomaly in the Energetic Particle Detector (EPD) channel in question. Therefore, the use by the authors of the EPD data to establish the presence of a plume during this pass is erroneous. Our conclusion is that during E26 the Galileo EPD data has to date not shown evidence of a plume. Key Points: The energetic proton flux decrease previously interpreted as the signature of a plume on the Galileo E26 flyby is an artifact There is yet no convincing evidence for a plume encounter on Galileo's E26 pass by Europa